Stressed and inflamed, can GSK3 be blamed? - Jope, Richard S. (Trends Biochem Sci, 2016)
Psychological stress has a pervasive influence on our lives. In many cases adapting to stress strengthens organisms, but chronic or severe stress is usually harmful. One surprising outcome of psychological stress is activation of an inflammatory response, resembling inflammation caused by infection or trauma. Excessive psychological stress and the consequential inflammation in the brain can increase susceptibility to psychiatric diseases, such as depression, and impair learning and memory, including in some patients with cognitive deficits. An emerging target to control detrimental outcomes of stress and inflammation is glycogen synthase kinase-3 (GSK3). GSK3 promotes inflammation, partly by regulating key transcription factors in the inflammation signaling pathway, and GSK3 can impair learning by promoting inflammation and by inhibiting long term potentiation (LTP). Drugs inhibiting GSK3 may prove beneficial for controlling mood and cognitive impairments caused by excessive stress and the associated neuroinflammation.